Pengaruh Pemberian Transcutaneous Electrical Nerve Stimulation (Tens) Terhadap Tingkat Nyeri Neuropati Pada Penderita Diabetes Mellitus Di Wilayah Kerja Puskesmas Sibela - Rahman, M. Esa Aditya; , Okti Sri Purwanti. S.Kep., M.Kep., Ns. Sp.Kep.M.B (2017)
Introduction Indonesia is a country that fulfill the order to 7 who have Diabetes Mellitus (DM) in the world as many as 8.5 million patients. The incidence of diabetes is high effect on increasing complications. One of the complications of diabetes is the Neuropathic diabetic. One non-pharmacological treatment for neuropathic pain is the use of transcutaneous electrical nerve stimulation (TENS). Giving TENS can reduce pain by increasing network vaskularisasai. The purpose of this study was to determine whether there is the effect of TENS on the level of neuropathic pain in patients with DM in Puskesmas Sibela. The research method using quasi-experimental study with a group control without randomization. The study was conducted in Puskesmas Sibela in March 2017. The samples were taken by 30 respondents with purposive sampling technique. The instrument used was a questionnaire TENS and measurement using the VAS pain scale. Data were analyzed using non-parametric Wilcoxon test and independent t-test test. The results showed the average level of pain before administration of TENS in the treatment group 5.53 and for the group control amounted to 4.93 and the average level of pain after being given TENS in the treatment group of 3.87 and 4.93 for the control group. The conclusion shows the influence of TENS on reduction of pain Neuropathic diabetic. Advice for health centers can use TENS as an alternative method of applying non-pharmacological pain management.